Analysis Of Teachers' Satisfaction Level As Users Of The e-Rapor Application Using The PIECES Framework Method (Case Study: SMK Swasta Panca Budi Medan) - maida (Journal of Information Technology, computer science and Electrical Engineering, 2024)
The e-Rapor application is a web-based application for processing student learning outcomes. When using the e-Rapor application at SMK Swasta Panca Budi Medan, teachers often encounter several obstacles. So an evaluation stage is needed for the use of the e-Rapor application at SMK Swasta Panca Budi Medan. The method used to evaluate the use of the e-Rapor application is the PIECES Framework. The PIECES Framework method is a method used to evaluate systems consisting of performance , information, economics, control and security, efficiency, and the service to be analyzed. Data was taken from the results of questionnaires for users of the e-Rapor application, namely teachers at SMK Swasta Panca Budi Medan, 39 teachers from various subjects as respondents. The research results show that the level of user satisfaction is SATISFIED in using the e-Rapor application.